Theories and Models of Alternative Energy and Their Socio-Economic Implications - Paul A. Comet (Emerging Issues in Environment, Geography and Earth Science Vol. 8, 2024)
There is a need for new political, social and economic theories, as neither present day capitalism nor communism are yet adequate in creating sustainable societies, or for reversing climate change. This is a rough “working” document for discussion purposes. Integrated responses are especially relevant to energy planning and implementation; interactions among water, food, energy and biological carbon sequestration; and urban planning, which provides substantial opportunities for enhanced resilience, reduced emissions and more sustainable development (medium confidence).